Accelerator room shielding in radiotherapy units where IMRT and TBI techniques are applied - Lesiak, Jan; Waligórski, Michał (Contemporary Oncology/Współczesna Onkologia, 2002)
New highly specialized radiotherapy techniques, such as IMRT (Intensity Modulated Radiation Therapy) or TBI (Total Body Irradiation), are being introduced, leading to an increased workload of medical accelerators. At the same time, modern radiotherapy centres are often being located or expanded in close vicinity of buildings serving other purposes. Also, more stringent radiation protection regulations concerning radiation workers are being implemented. Thus, in order to fulfill the requirements of radiation protection, the influence of the increase in the workload of medical accelerators on the thickness of their permanent shielding must be considered. The aim of this work is to evaluate, using calculated examples, the dependence of the required thickness of permanent biological shielding of the medical accelerator on the range of application of highly specialized radiotherapy techniques, such as IMRT or TBI, performed using this accelerator. It is concluded that the technical specifications of the design of a new radiotherapy laboratory should include the proposed contribution of IMRT and TBI procedures. Existing shielding in currently operating laboratories which has been designed only for conventional radiotherapy may not be sufficiently thick. In this case, appropriate thickening of the current shielding may be necessary, or, alternatively, a planned limitation of the number of patients irradiated using this accelerator.